The relationship between work ethics and power sources of managers with job satisfaction of employees of the General Directorate of Sports and Youth of Albasra province. - Dhafer Obaid Faraj (Peerian Journals Publishing, 2023)
Satisfaction in all situations is considered a competitive advantage for organizations. The present study was conducted with the aim of investigating the relationship between work ethics and power sources of managers with job satisfaction of employees of the General Department of Sports and Youth in Albasra province. Based on the sample size determination table of Albasra province, 127 employees of the General Department of Sports and Youth of Albasra province answered the standard questionnaires of work ethics (Petty, 1990), managers' sources of power (Van et al., 2000) and job satisfaction (Lins, 2003). Completed the stratified-random design. The analysis of the collected data was done using appropriate descriptive and inferential statistics, including Pearson's correlation to determine simple relationships and multivariate regression to predict the relationships of the variables using SPSS software. The findings showed that between the variables There is a positive and significant relationship between work ethics and job satisfaction, power and job satisfaction, power and work ethics. Also, the results showed that work ethics is a good predictor for employees' job satisfaction and power sources cannot be a good predictor for job satisfaction. In total It can be said that since the main capital of any organization is the human resources of that organization and the two pillars of the manager and the employees are decisive in obtaining the desired results, therefore, the selection of appropriate methods of exercising power and work ethics by the managers can lead to job satisfaction. be employees, a It will surely increase the success of organizations and the realization of their goals.
Keywords: Work ethics; job satisfaction; power sources; sports